The Superoxide Dismutase Gene Family in Nicotiana tabacum: Genome-Wide Identification, Characterization, Expression Profiling and Functional Analysis in Response to Heavy Metal Stress - Huo, Chunsong; He, Linshen; Yu, Ting; Ji, Xue; Li, Rui; Zhu, Shunqin; Zhang, Fangyuan; Xie, He; Liu, Wanhong (Frontiers in Plant Science, 2022)
Superoxide dismutases (SODs) play an important role in protecting plants against ROS toxicity induced by biotic and abiotic stress. Recent studies have shown that the SOD gene family is involved in plant growth and development; however, knowledge of the SOD gene family in tobacco is still limited. In the present study, the SOD gene family was systematically characterized in the tobacco genome. Based on the conserved motif and phylogenetic tree, 15 NtSOD genes were identified and classified into three subgroups, including 5 NtCSDs, 7 NtFSDs and 3 NtMSDs. The predicted results of the transport peptide or signal peptide were consistent with their subcellular localization. Most NtSOD genes showed relatively well-maintained exon-intron and motif structures in the same subgroup. An analysis of cis-acting elements in SOD gene promoters showed that NtSOD expression was regulated by plant hormones, defense and stress responses, and light. In addition, multiple transcription factors and miRNAs are predicted to be involved in the regulation of NtSOD gene expression. The qPCR results indicated specific spatial and temporal expression patterns of the NtSOD gene family in different tissues and developmental stages, and this gene family played an important role in protecting against heavy metal stress. The results of functional complementation tests in the yeast mutant suggested that NtCSD1a, NtFSD1e and NtMSD1b scavenge ROS produced by heavy metal stress. This study represents the first genome-wide analysis of the NtSOD gene family, which lays a foundation for a better understanding of the function of the NtSOD gene family and improving the tolerance of plants to heavy metal toxicity.